Event Marketing, Stakeholder Engagement, and Customer Loyalty in the Hotel Sector: The Mediating Role of Customer Satisfaction in South East Nigeria - Chieloka James Mokwuah; Emeka Kenechi Agina (International Journal of Home Economics, Hospitality and Allied Research, 2025)
The hotel sector of the hospitality industry appears to be growing at a tremendous rate as number of hotels in the south east have continued to grow. These hotels endeavor to provide food, shelter, accommodation, entertainment, and leisure for guests. Due to an intense competition in the sector, hotels are now faced with the problem of unoccupied rooms and high overheads cost. This problem requires proactive engagement with customers through event marketing and stakeholder engagement in order to satisfy them and make them loyal. The objectives of the study are to: examine the mediating role of customer satisfaction on the relationship existing between event marketing and customer loyalty in the hospitality industry; examine the mediating role of customer satisfaction on the relationship existing between stakeholder engagement and customer loyalty in the hospitality industry. Survey research design was adopted for the study with a structured questionnaire used for data collection from a sample of 396 customers/quests. A two-shaped structural equation modeling procedure was applied to analyse and test the hypotheses. The finding of the study revealed that customer satisfaction has a statistically significant mediating role on the relationship existing between event marketing and customer loyalty, and the mediating role of customer satisfaction is statistically not significant on the relationship between stakeholder engagement and customer loyalty. In conclusion, in order to maintain the current customer of hotels and satisfy them, there is a need to integrate engagement practices such as event marketing in order to satisfy the customers, and enhance their loyalty.